1994
DOI: 10.1016/0012-821x(94)90262-3
|View full text |Cite
|
Sign up to set email alerts
|

Isotopic variations with distance and time in the volcanic islands of the Cameroon line: evidence for a mantle plume origin

Abstract: The oceanic sector of the Cameroon line consists of three volcanic islands: Principe, Silo Tome and Pagalu. New 4°Ar-39Ar data for Pagalu basalts, combined with published K-Ar ages for Principe and S~to TomE, indicate that all three islands have been active in the past 5 Ma. They have similar petrogenetic histories, with basements of basaltic flows capped by more evolved rocks. However, the age of the earliest exposed volcanic rocks decreases occanward from Principe (31 Ma) to Sao Tome (13 Ma) to Pagalu (4.8 M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
159
0
15

Year Published

1999
1999
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 228 publications
(212 citation statements)
references
References 48 publications
7
159
0
15
Order By: Relevance
“…Volcanism continues to the present at both onshore and offshore volcanic centers. Although there is no evidence for age progression of volcanics along the onshore portion of the CVL [e.g., Hedberg, 1969;Grant et al, 1972;Grunau et al, 1975;Dunlop and Fitton, 1979;Cornen and Maury, 1980;Dunlop, 1983;Fitton and Dunlop, 1985;Lee et al, 1994;Ngounouno et al, 1997;Marzoli et al, 1999Marzoli et al, , 2000Ngounouno et al, 2001Ngounouno et al, , 2003Njilah et al, 2004;Ngounouno et al, 2005Ngounouno et al, , 2006Aka et al, 2009;Dongmo et al, 2010;Kamgang et al, 2010], some studies have suggested a possible seaward progression for the oceanic sector; however, this possibility remains unclear due to small numbers of samples [Grunau et al, 1975;Meyers and Rosendahl, 1991;Meyers et al, 1998]. Volcanics throughout the CVL consist primarily of alkaline basalts [Hedberg, 1969].…”
Section: The Cameroon Volcanic Linementioning
confidence: 99%
See 3 more Smart Citations
“…Volcanism continues to the present at both onshore and offshore volcanic centers. Although there is no evidence for age progression of volcanics along the onshore portion of the CVL [e.g., Hedberg, 1969;Grant et al, 1972;Grunau et al, 1975;Dunlop and Fitton, 1979;Cornen and Maury, 1980;Dunlop, 1983;Fitton and Dunlop, 1985;Lee et al, 1994;Ngounouno et al, 1997;Marzoli et al, 1999Marzoli et al, , 2000Ngounouno et al, 2001Ngounouno et al, , 2003Njilah et al, 2004;Ngounouno et al, 2005Ngounouno et al, , 2006Aka et al, 2009;Dongmo et al, 2010;Kamgang et al, 2010], some studies have suggested a possible seaward progression for the oceanic sector; however, this possibility remains unclear due to small numbers of samples [Grunau et al, 1975;Meyers and Rosendahl, 1991;Meyers et al, 1998]. Volcanics throughout the CVL consist primarily of alkaline basalts [Hedberg, 1969].…”
Section: The Cameroon Volcanic Linementioning
confidence: 99%
“…Although some studies have suggested this as a possible source for the CVL (Figure 13a) [e.g., Morgan, 1983;Van Houten, 1983;Lee et al, 1994;Burke, 2001], geochemical studies indicate a lack of age progression along the line, making this simple hot spot model an unlikely source for the CVL [e.g., Hedberg, 1969;Grant et al, 1972; …”
Section: Models For the Formation Of The Cameroon Volcanic Linementioning
confidence: 99%
See 2 more Smart Citations
“…Instead, volcanic centers along the entire length of the chain have recently been active [Fitton and Dunlop, 1985]. However, initiation of volcanism in the ocean islands shows a pattern of outward progression, where basaltic rocks in the basal portions of each subaerial stratigraphic sequence become younger with distance from the COB, e.g., Prfncipe, 31 Ma; S•o Tom& 13 Ma; and Annobon, 4.8 Ma [Lee et al, 1994]. Lee et al [1994] interpret this feature as the outward propagation and lengthening of a sublithospheric "hot zone.…”
Section: Introductionmentioning
confidence: 99%